Meningkatkan Keterampilan Menulis Narasi Melalui Model Pembelajaran PjBL Berbantuan Media Gambar Tunggal Pada Peserta Didik Kelas IV SD Negeri 1 Kedungwuluh - Muhammad Dian Alkautsar Prasetyo; Pamujo Pamujo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study was motivated by the low narrative writing skills of the students in Class IVB at SD Negeri 1 Kedungwuluh, particularly in developing ideas, structuring a coherent plot, and using language that adheres to grammatical rules. These conditions indicate the need for innovation in teaching to help students become more active and focused in their writing. This study aims to improve narrative writing skills through the application of the Project-Based Learning (PjBL) model supported by single-image media. The method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of two sessions with stages of planning, implementation, observation, and reflection. The research subjects consisted of 24 students. Research instruments included learning materials and student worksheets, while data analysis was conducted using descriptive qualitative and quantitative methods. The results showed an improvement in narrative writing skills in each cycle. The achievement rate in developing story outlines increased from 62.5% in Cycle I to 83.3% in Cycle II. Additionally, the ability to develop a story outline into a complete narrative text increased from 66.67% to 87.5%. This improvement confirms that the application of the Project-Based Learning model supported by a single image is effective in improving students’ narrative writing skills.